1972
DOI: 10.1192/bjp.121.3.241
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Family Life on the Course of Schizophrenic Disorders: A Replication

Abstract: In spite of the new methods of treatment and care introduced during the past fifteen years, schizophrenic patients are still liable to relapse with a recurrence of florid symptoms such as delusions, hallucinations and disturbed behaviour, and great suffering can be caused to all concerned (Brown et al., 1966). It has been shown that the onset of florid symptoms is often preceded during the previous three weeks by a significant change in the patient's social environment (Brown and Birley, 1968; Birley and Brown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
774
3
78

Year Published

1974
1974
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,682 publications
(880 citation statements)
references
References 15 publications
25
774
3
78
Order By: Relevance
“…They also found that ratings of EE were significantly associated with lower social functioning particularly with hostility, but they did not explore the differences between the sexes in their study. Indeed, males and females are expected to be equally distributed in high EE homes 24 but more males return to conflicting environments after hospital discharge 4,25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also found that ratings of EE were significantly associated with lower social functioning particularly with hostility, but they did not explore the differences between the sexes in their study. Indeed, males and females are expected to be equally distributed in high EE homes 24 but more males return to conflicting environments after hospital discharge 4,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Brown et al 4 conducted a longitudinal prospective study in 101 inpatients with schizophrenia or related disorders by PSE to test if a high degree of Expressed Emotion (EE) would be a predictive factor of relapse. The feelings expressed by relatives were measured by means of a semi-structured interview which attributed ratings based on vocal aspects of speech, such as tone and pitch, and on the content of the relative's report.…”
Section: Introductionmentioning
confidence: 99%
“…Não há evidência de que a cronicidade dos pacientes seja fator prognóstico de recaída. Vários estudos indicam que a emoção expressa (variável que associa medidas de criticismo, hostilidade e intrusão -superenvolvimento) do familiar em relação ao paciente 28,29,30,31,32 é um fator prognóstico de recaída. c) As etapas do processo de cegamento, nesse caso, cegamento da alocação e do avaliador.…”
Section: Diagnostic and Statistical Manual Of Mental Disorders Fourtunclassified
“…As definições e medidas de recaída usadas pelos ensaios foram avaliadas tendo como parâmetro a proposta de Brown et al 29 : recaída tipo I -recorrência de sintomas em pacientes que estavam sem sintomatologia ao início do estudo, e recaída tipo II -aumento no número e intensidade de sintomas para aqueles pacientes que tinham sintomas esquizofrênicos ativos ao início do estudo. O evento suicídio foi considerado recaída 33 .…”
Section: Diagnostic and Statistical Manual Of Mental Disorders Fourtunclassified
“…The construct of EE is comprised of three components: critical comments made by a relative about the patient, hostility and marked emotional response (Brown et al, 1972). More recently Rylands et al (2011) found that high EE stimuli activated brain regions responsible for processing socially aversive information in schizophrenic patients.…”
Section: Introductionmentioning
confidence: 99%